Strategi Internal Public Relations PT Melia Sehat Sejahtera Dalam Menjaga Hubungan Karyawan - Tanjung, Regina Eka Wulandari; Rorong, Michael Jibrael (LPPM Universitas Putera Batam, 2022)
The internal strategy for public relations at PT Melia Sehat Sejahtera is to maintain employee relations. Inthis case employees are one of the most important informants within a company so that the importance ofgood relations within an organization or company in carrying out management organization rotation both inthe internal and external scope of the company so that the foundation factory is a management function thatbridges between companies and the media public. While the research method used in this study is usingqualitative research methods with the object of study at PT Melia Sehat Sejahtera. The results of this studyindicate that PT Melia is healthy and prosperous in relation to the internal public relations strategy at the PT,namely that there are aspects of employee relations in the form of internal communication in bridgingemployees. Meanwhile, the strategic aspect of internal public relations at the PT is the existence of alearning system that is given to members or employees. Of course, this is supported by internal publicrelations communications carried out by PT Melia Sejahtera in internalizing internal public relations relationsat PT Milea Sehat Sejahtera